Learning development in higher education - Hartley, Peter; Hilsdon, John.; Keenan, Christine; Sinfield, Sandra; Verity, Michelle (Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
This book shows how learning development enhances the student experience and promotes active engagement. Written by staff from the UK's largest collaborative Centre for Excellence in Teaching and Learning (CETL), the book includes insights for everyone interested in supporting student retention, progression and success.
What is learning development? / John Hilsdon -- Learning development in higher education: community of practice or profession? / Bob Glass and Linda Murray -- Is learning development "part of the problem"? / Ann Barlow, John Ackroyd and Alyssa Philips -- Raising the student voice / Sandra Sinfield ... [et al.] -- A PDP perspective on supporting students through transition into HE / Christine Keenan -- Learning developers supporting early student transition / Ed Foster, Sarah Lawther, and Jane McNeil -- The case for one to one academic advice for students / Judy Turner -- The assignment success programme / Martin Sedgley -- Enabling transitions through inclusive practice / Val Chapman -- Building student confidence in maths and numeracy / Mundeep Gill and Martin Greenhow -- Negotiating and nurturing: challenging staff and student perspectives of academic writing / Rebecca Bell -- Learning resources that students will use: producing a web based multimedia resource to improve group working skills / Carol Elston, Peter Hartley, and Julia Braham -- The student as producer: learning by doing research / Andy Hagyard and Sue Watling -- Visualising learning / Pauline Ridley -- When worlds collide: learning development and e-learning / Bob Glass, Debbie Holley, and Sandra Sinfield -- Defining and supporting the new digital students / Neil Currant, Becka Currant, and Peter Hartley -- The focus of attention: distractions from study for the generation Y student / Kim Shahabudin -- Learning from the past and looking into the future / Michelle Verity and Paul Trowler -- Learning development: work in progress / John Hilsdon, Christine Keenan, and Sandra Sinfield.
Keywords: College teaching; Learning strategies